2020
DOI: 10.1002/mgg3.1300
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of genetic variants in children with long QT syndrome

Abstract: Background Genes encoding cardiac ion channels or regulating proteins have been associated with the inherited form of long QT syndrome (LQTS). Complex pathophysiology and missing functional studies, however, often bedevil variant interpretation and classification. We aimed to evaluate the rate of change in variant classification based on current interpretation standards and dependent on clinical findings. Methods Medical charts of children with a molecular genetic diagnosis of LQTS presenting at our centers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…The rate of CEs among LQT1 and LQT2 patients in post-adolescence was not presented due to a lack of sufficient evidence ( Figure 2C). Thus, appropriate stratification in terms of the above factors should be performed, in order to guide clinical decision-making for BBs therapy and improve the prognosis of LQTS with the minimum adverse-events (Migdalovich et al, 2011;Westphal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of CEs among LQT1 and LQT2 patients in post-adolescence was not presented due to a lack of sufficient evidence ( Figure 2C). Thus, appropriate stratification in terms of the above factors should be performed, in order to guide clinical decision-making for BBs therapy and improve the prognosis of LQTS with the minimum adverse-events (Migdalovich et al, 2011;Westphal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We furthermore systematically evaluated the efficacy of BBs therapy in LQTS with different ages, genders, and QTc intervals, as well as genetic subtypes ( Bohnen et al, 2017 ). It is well-established that the rate of CEs in LQTS patients is closely correlated with age and sex ( Wang and Wu, 2004 ). Previous reports have indicated that the risk of fatal events in LQTS is higher in boys than girls during childhood ( Goldenberg et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study focused on a cohort of children diagnosed with LQTS, 66.66% of VUS were reclassified as LP/P (Bennett et al 2019). In contrast, another study reported 14.3% of variants previously classified as LP/P were downgraded to VUS (Westphal et al 2020). This ambiguity reinforces the need for additional studies focused on a proper reinterpretation, especially if variants were not originally classified following ACMG recommendations (Campuzano et al 2020a, b;VanDyke et al 2020).…”
Section: Long Qt Syndromementioning
confidence: 99%
“…In a study focused on a cohort of children diagnosed with LQTS, 66.66% of VUS were reclassi ed as LP/P (Bennett et al, 2019). In contrast, another study reported 14.3% of variants previously classi ed as LP/P were downgraded to VUS (Westphal et al, 2020). This ambiguity reinforces the need for additional studies focused on a proper reinterpretation, especially if variants were not originally classi ed following ACMG recommendations (Campuzano, Sarquella-Brugada, Fernandez-Falgueras, et al, 2020, VanDyke et al, 2020.…”
Section: Long Qt Syndromementioning
confidence: 99%